Correlation between Fasting Lipid, Total Body Fat, Body Mass Index and Thyroid Status Among Patients with Thyroid Disorders - Ishak, Fatimah Mastura; Haron, Juhara; Wan Mohamed, Wan Mohd Izani; Tuan Ismail, Tuan Salwani (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Thyroid dysfunction affects lipid metabolism via lipoprotein transport. In this study, we compared the fasting lipid profile, body mass index and percentage of total body fat among patients with different thyroid status and its correlation with thyroid function test. MATERIALS AND METHODS: We conducted a cross sectional study over 28 months among patients with different thyroid status from Oncology Clinic and Endocrine Clinic at Hospital Universiti Sains Malaysia. Adult patients age 18 years to 80 years, hyperthyroid at least 6 months or hypothyroid at least 6 months or euthyroid at least 1 year were eligible. The total percentage of body fat was measured using DEXA scan. The thyroid function test and fasting lipid profiles were documented. Comparison of fasting lipid profile, BMI and percentage of total body fat among different thyroid status was performed using one-way ANOVA. Pearson correlation was used to analyse the aforementioned variables with the thyroid function test (TSH and free T4). RESULTS: A total of 159 patients were recruited. The majority were Malays (93.1%), female (68.6%) and hyperthyroid (42.8%). There was no significant mean difference of triglyceride (TG), total cholesterol (T-Chol), LDL, HDL, BMI and percentage of total body fat among patients with different thyroid status (p>0.050). Among hypothyroid patients, T-Chol and HDL were positively correlated with TSH (r=0.43, r=0.36) but inversely correlated with free T4 (r=-0.42, r=-0.39). The free T4 was inversely correlated with the percentage of total body fat among patients with euthyroid status (r=-0.50). The TSH was negatively correlated with the percentage of total body fat among patients with hyperthyroid status (r=-0.28). CONCLUSION: A positive correlation between TSH with T-Chol and negative correlation between T4 with T-Chol among hypothyroidism status suggests a potential reduction of risk in the cardiovascular event among this group.